2000
DOI: 10.1083/jcb.150.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Hydrolysis to Ceramide during the Execution Phase of Apoptosis Results from Phospholipid Scrambling and Alters Cell-Surface Morphology

Abstract: Apoptosis is generally accompanied by a late phase of ceramide (Cer) production, the significance of which is unknown. This study describes a previously unrecognized link between Cer accumulation and phosphatidylserine (PS) exposure at the cell surface, a characteristic of the execution phase of apoptosis resulting from a loss of plasma membrane phospholipid asymmetry. Using a fluorescent sphingomyelin (SM) analogue, N-(N-[6-[(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]caproyl]–sphingosylphosphorylcholine (C6-NBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
143
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(164 citation statements)
references
References 64 publications
19
143
0
2
Order By: Relevance
“…93 The induction of ceramide appears to be secondary to induction of both acidic and neutral sphingmyelinases. Although recent evidence has pointed to phospholipid scrambling in the plasma membrane as the mechanism of sphingomyelin activation during apoptosis, 94 studies in corticosteroid-treated thymocytes suggest that sphingomyelinase activation and ceramide generation proceed by a different mechanism. 93 In thymocytes, dexamethasone treatment rapidly induces diacylglycerol through a protein kinase C and G-proteindependent phosphatidylinositol-specific phospholipase C (PI-PLC).…”
Section: Sphingomyelin Hydrolysis and Ceramidementioning
confidence: 99%
“…93 The induction of ceramide appears to be secondary to induction of both acidic and neutral sphingmyelinases. Although recent evidence has pointed to phospholipid scrambling in the plasma membrane as the mechanism of sphingomyelin activation during apoptosis, 94 studies in corticosteroid-treated thymocytes suggest that sphingomyelinase activation and ceramide generation proceed by a different mechanism. 93 In thymocytes, dexamethasone treatment rapidly induces diacylglycerol through a protein kinase C and G-proteindependent phosphatidylinositol-specific phospholipase C (PI-PLC).…”
Section: Sphingomyelin Hydrolysis and Ceramidementioning
confidence: 99%
“…41 In fact, ceramide formation with concomitant sphingomyelin hydrolysis appears to be necessary for the changes in membrane morphology (eg blebbing, vasculization, and externalization of phosphatidylserine) that are the hallmark features of the execution phase of apoptosis. 42 In addition to its metabolic and structural roles, it is becoming increasingly clear that ceramide plays a critical role in transmembrane signaling, particularly in response to stress challenges. [5][6][7][8][9][10][11] Therefore, it is not surprising that there are multiple physiologic pathways that produce ceramide.…”
Section: Ceramide Is Generated By Multiple Metabolic Pathwaysmentioning
confidence: 99%
“…1 PS externalization can, in some cases, be divorced from membrane blebbing; however, macrophage engulfment of PS-positive cell corpses appears to be less efficient when blebbing is prevented (unpublished findings). An interesting twist to the story was added when Tepper et al 12 reported that blebbing during apoptosis is related to sphingomyelin (SM) hydrolysis to ceramide and the loss of phospholipid asymmetry in the plasma membrane. Hence, ceramide production during the execution phase of apoptosis was shown to be derived from SM initially located in the outer leaflet of the plasma membrane, which gains access to a cytosolic SMase by flipping to the inner leaflet in a process of lipid scrambling.…”
Section: Ps Signaling Is Required For Programmed Cell Clearancementioning
confidence: 99%